Pelatihan Penulisan Artikel Ilmiah untuk Pengembangan Karir Guru Matematika di Kabupaten Bojonegoro - Dewi Utami, Anita; Zainudin, M; Suriya, Puput; Mayasari, Novi; Hasanudin, Cahyo; Rosyida, Fathia (Institut Teknologi dan Bisnis Riau Pesisir, 2021)
Abstract The PKM program for writing scientific articles to improve the careers of mathematics teachers in Bojonegoro was carried out through the method of providing training, guidance, and mentoring to participants on how to write articles on the results of classroom action research that was carried out daily in their classrooms to make scientific articles that can be published in journals. The main target audience in this activity were mathematics teachers under the auspices of the Bojonegoro Ministry of Religion, totaling 30 teachers. The area where the training and workshop location was at MAN 2 Bojonegoro is a gathering place for mathematics teachers in the MGMP organization. The results in the PKM program activities were (1) increased knowledge of scientific articles, (2) increased ability and skills of participants in writing scientific articles from the results of classroom action research and (3) participants can integrate scientific writing in the learning process. The outputs of this PKM activity were (1) increasing participants' knowledge of the activity materials, (2) scientific articles published in national seminars or national journals, and (3) publication of PKM implementation on online media. Abstrak Program PKM penulisan artikel ilmiah untuk peningkatan karir guru matematika di Bojonegoro dilakukan melalui metode pemberian pelatihan, bimbingan, dan pendampingan kepada peserta mengenai bagaimana cara menulis artikel hasil penelitian tindakan kelas yang dilakukan sehari-hari dalam kelasnya untuk dibuat suatu artikel ilmiah yang dapat terbit di jurnal.. Khalayak sasaran utama dalam kegiatan ini yaitu guru-guru matematika di bawah naungan Kemenag Bojonegoro yang berjumlah 30 guru. Wilayah lokasi pelatihan dan workshop di MAN 2 Bojonegoro sebagai tempat berkumpulnya para guru matematika dalam organisasi MGMP. Hasil dalam kegiatan program PKM yaitu (1) meningkatnya pengetahuan mengenai artikel ilmiah, (2) meningkatnya kemampuan dan keterampilan peserta dalam menulis artikel ilmiah dari hasil penelitian tindakan kelas dan (3) peserta dapat mengintergrasikan karya tulis ilmiah dalam proses pembelajaran. Luaran kegiatan PKM ini yaitu (1) meningkatnya pengetahuan peserta mengenai materi-materi kegiatan, (2) artikel ilmiah yang dipublikasikan pada seminar nasional atau jurnal nasional, dan (3) publikasi pelaksanaan PKM pada media online.